Доля Богдана — рідного брата Степана Бандери - Ковальчук, В. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2009)
Based on unknown documents of former Soviet secret services, the author reconstructed the milestone of Bohdan Bandera’s life.